2008
DOI: 10.1021/jp077107u
|View full text |Cite
|
Sign up to set email alerts
|

Proton Dynamics in the Strong Chelate Hydrogen Bond of Crystalline Picolinic Acid N-Oxide. A New Computational Approach and Infrared, Raman and INS Study

Abstract: Infrared, Raman and INS spectra of picolinic acid N-oxide (PANO) were recorded and examined for the location of the hydronic modes, particularly O-H stretching and COH bending. PANO is representative of strong chelate hydrogen bonds (H-bonds) with its short O...O distance (2.425 A). H-bonding is possibly well-characterized by diffraction, NMR and NQR data and calculated potential energy functions. The analysis of the spectra is assisted by DFT frequency calculations both in the gas phase and in the solid state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 57 publications
(95 reference statements)
2
75
1
Order By: Relevance
“…Further, the Troullier-Martins (TM) pseudopotential [73] with a wavefunction cutoff of 70 Ry is adopted to describe the interaction between the core and valence electrons in the quantum region. Note that BLYP, together with the plane wave base set, has been reported to yield good results for the simulation of a hydrogen-bonded system, such as liquid water [74], liquid HF [75] and strong HB in crystalline picolinic acid N-oxide [40].…”
Section: Simulation Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the Troullier-Martins (TM) pseudopotential [73] with a wavefunction cutoff of 70 Ry is adopted to describe the interaction between the core and valence electrons in the quantum region. Note that BLYP, together with the plane wave base set, has been reported to yield good results for the simulation of a hydrogen-bonded system, such as liquid water [74], liquid HF [75] and strong HB in crystalline picolinic acid N-oxide [40].…”
Section: Simulation Detailsmentioning
confidence: 99%
“…In other words, a quantitative result would not be expected from this approach. An alternative approach is the on-the-fly calculation of NH stretching snapshot potentials in a frozen environment for some representative configurations along the trajectory [37][38][39][40]. To accomplish this goal, geometry snapshots in the time interval 1.0-9.0 ps are sampled at typical long, short and intermediate base-pair separations for the computation of potential curves.…”
Section: Nh Stretching-hb Length Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, harmonic frequency calculations at B3LYP/6-311++G(3df, 3pd), B3LYP/6-31+G(d, p) and B3LYP/6-31G(d, p) levels yield O-H stretching frequencies ν OH of 2977 cm −1 [25], 2965 cm −1 [84], and 2991 cm −1 [85] respectively. In the experimental infrared spectrum of PANO isolated in an Ar matrix, however, Szczepaniak et al [85] found no intense absorption band within 1200 cm [86]. Here, we present a 2D analysis using the potential surfaces for PANO calculated by Stare and Balint-Kurti [25] and by Stare and Mavri [84].…”
Section: D Hénon-heiles Potentialmentioning
confidence: 83%
“…The theory presented by Yaremko et al takes into account FermiDavydov resonance and interaction of the H-bond vibrations with the lattice phonons but this theory applied to adipic acid crystal reproduces only the main features of the experimental spectra. Crystal field effects and thermal fluctuations were recently incorporated in simulations of spectra of hydrogen-bonded systems using the Car-Parinello method [37][38][39] but this approach is computationally expensive and limited to quantization of few degrees of freedom. Our quantum-mechanical model considers major vibrational interactions in hydrogen-bonded systems, treats the broadening as a phenomenological process, and allows for quantitative reproduction of experimental spectra of hydrogenbonded systems and their deuterated analogs [32,40,41].…”
Section: Resultsmentioning
confidence: 99%